Managing undertreated chronic cancer pain and non cancer pain in husm multidisciplinary chronic pain service (MCPS) - Abdul Aziz, Jusoh (2011)
Chronic pain is a serious problem in the community. Among patients received treatment in HUSM, many patients that had been admitted into the wards for various primary conditions had continuous pain despite of treatments given which causing poor satisfaction among patients. Chronic pain can be defined as prolonged pain sensation at any body part and usually lasting for more than one to three months. Chronic pain can be broadly classified into two main types, chronic cancer pain and non cancer pain. It is paramount important to identifY the source of pain and dominant type of pain in order to give a precise and effective treatments. In this research, we want to have a picture regarding the seriousness of the incidence of undertreated for both chronic cancer pain and non cancer pain and to identify the possible contributing factors that lead to it. At the same time, we want to evaluate the effectiveness of HUSM MCPS in providing treatment for the undertreated chronic cancer pain and non cancer pain patients. This a Prospective Cohort Study that is aiming to get an overall percentage of undertreated chronic cancer pain and non cancer pain among patients admitted into oncology and surgical based wards. The possible contributing factors that may lead to the undertreatment among cancer pain patients and non cancer pain patients will be determined and recommendations to overcome the identified problem will be presented at the end of this research. The relationship between demographic data and the occurrence of the undertreated among chronic cancer pain and non cancer pain also will be presented. The last objective is to evaluate the effectiveness of treatment provided by HUSMMCPS. A total of one hundred and three chronic cancer pain patients and fourty seven chronic non cancer pain patients were required in order to get power of study with 80% confidence interval. All the patients involved were those admitted into oncology and surgical based wards in HUSM. The cohorts was divided into two, chronic cancer pain and non cancer pain. Both groups were assessed and treated by HUSM MCPS headed by a pain specialist. Based on criteria predetermined, both categories of patients were categorized as undertreated or not undertreated. The percentage of undertreated was determined for both groups of patients. All the undertreated patients were received treatments by HUSM MCPS according to their pain diagnosis given by pain specialist and responses toward treatment given were recorded. The responses were assessed in term of improvement in pain score using visual analogue score (VAS) and disability score using Modified Rolland & Morris Disability score (MRMD). For pain score, any score of four and above was considered as poor pain control and score three and below was considered as good pain control. All patients were treated and periodically seen until their pain score become three or less. The improvement in MRMD score is taken when the pain score is at three or less. The effectiveness of treatment given by HUSM MCPS was evaluated based on time taken to reduce pain score to three or less and how much the improvement in disability guided by score of MRMD. The maximum time for each patient followed up was six months. Any patient that requires time longer than six months to reduce his or her pain score to three or less was considered having refractory pain.